Analysis of ARQ protocols via signal flow graphs - Lu, D.-L.; Chang, J.-F. (IEEE transactions on communications, 1989)
A unified methodology using signal flow graphs is proposed and used to analyze several existing ARQ (automatic repeat request) protocols. The methodology offers a systematic and efficient way of obtaining throughput and delay. It also offers additional advantages in obtaining results such as the mean response time, and in analyzing the ARQ protocols in which the feedback channel is not error-free.< >